Comparison of carbon nanotube deposition on HfB2, ZrB2, and TiB2 by chemical vapor decomposition. (September 2021) - Lin, Jia; Jin, Hua; Ge, Xiaohong; Yang, Yihang; Huang, Guimei; Wang, Jinhuo; Li, Fenqiang; Li, Hui; Wang, Shuai
Abstract: CNTs were successfully synthesized on refractory metal diborides (HfB2, ZrB2, and TiB2 ) via CVD, with Ni as the catalyst at about 850–1200 °C. The obtained powders were densified via SPS at 1400–1700 °C to obtain a composite. The microstructures of the grown CNTs were characterized. The mechanical performances of the as-received materials were tested to evaluate the enhancing impact of CNTs grown in situ. Phase analysis of the final materials was conducted by XRD to eliminate the effects of impurities. The optimal strength and toughness, respectively, were 1013 ± 48 MPa and 10.7 ± 0.5 MPa·m 1/2 for TiB2 -Ni-CNT composites; 988 ± 47 MPa and 9.4 ± 0.4 MPa·m 1/2 for ZrB2 -Ni-CNT composites; and 912 ± 43 MPa and 8.5 ± 0.3 MPa·m 1/2 for HfB2 -Ni-CNT composites. The CNTs grown in the boride matrix exhibited uniform dispersion, resulting in further enhancement.